CPFD modeling and experimental validation of gas–solid flow in a down flow reactor. (12th July 2016) - Lanza, A.; Islam, M.A.; de Lasa, H.
Graphical abstract: Highlights: We studied gas–solid fluid dynamics in the developed region of a downer unit. We simulated particle–fluid flow using CPFD Barracuda software. We considered a random particle selection for cluster formation in the CPFD model. We studied cluster size distributions for a CPFD model with experimental data. We validated the computational model using a wide range of operating conditions. Abstract: This manuscript reports the fluid dynamics in the developed flow region of a cocurrent gas–solid down flow fluidized bed unit. Gas–solid flows are simulated using a Computational Particle Fluid Dynamics (CPFD) numerical scheme and experimental data from the CREC-GS-Optiprobes. This model represents clusters in a downer unit. It is hypothesized that in downers, clusters are formed via a Random Particle-Selection Method (RPSM) ensuring cluster dynamic stability. To accomplish this, a statistical particle-selection of clusters (SPSC) method is developed. This hybrid model is validated with experimental data obtained in a 2 m height and 2.57 cm diameter column. Observed time-averaged axial and radial velocities and solid concentration profiles are successfully simulated by the Hybrid CPFD / CREC - GS - Optiprobes Data Model . These findings support: (a) a narrow distribution of particle cluster residences, (b) the relatively flat radial solid concentrations and solid cluster velocities, and (c) a valuable approach for establishing slip velocities in downer units.